Examination of health-seeking behavior, e-health literacy, and successful aging in older people. - Aydin, Gizem Zevde; Özer, Özlem; Özkan, Okan (Journal of Human Behavior in the Social Environment, 2025)
The present research aimed to investigate the correlation between health-seeking behavior, e-health literacy, and successful aging variables. The study population consisted of individuals aged 65 and over in Samsun province of Turkey. The study data were collected by the survey method between November 1–30, 2022, and the data obtained from 773 people were evaluated with various statistical methods. The regression analysis determined that health-seeking behavior explained 20.1% of the total variance on successful aging, e-health literacy explained 28.3% of the total variance on successful aging, and e-health literacy explained 34.6% of the total variance on health-seeking behavior.